Less talk, more action (Re)Organising universities in Aotearoa New Zealand - Simpson AB; Salter LA; Roy R; Oldfield LD; Simpson ADJ (Massey University, 2023)
Despite the growing size of the academic precariat in the tertiary sector, this exploited group of workers lacks a voice in either their universities or their national union. In this article we draw on our experiences of transitioning from a small activist group to a broader research collective with influence and voice, while forging networks of solidarity. Through reflecting on developing the Precarious Academic Work Survey (PAWS), we explore how action research is a viable way of structurally and politically (re)organising academic work. We argue that partnering with changemakers such as unions as co-researchers disrupts their embedded processes so that they may be (re)politicised towards pressing issues such as precarity. Further, we highlight how research can be used as a call to action and a tool to recruit powerful allies to collaborate on transforming universities into educational utopias.